Investigation of Physical Activity of Class IIA Prison Employees Kendal Regency - Kurnia Syarofi Fa’iq; Wiga Nurlatifa Romadhoni (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to analyze the level of physical activity among male employees at the Class IIA Kendal District Correctional Institution to support the implementation of security and community service tasks. This study uses a descriptive quantitative approach with the instrument being the International Physical Activity Questionnaire (IPAQ) to measure the level of physical activity. The population and sample of the study consist of 30 male employees. The analysis results show that the majority of employees fall into the low physical activity category (46.67%). As many as 36.67% of employees have a moderate level of physical activity, and only 16.66% fall into the high physical activity category. These findings indicate that the majority of male employees have not yet reached an optimal level of physical activity to support job demands that require physical readiness, stamina, and body endurance. The low level of physical activity can negatively impact the work performance and long-term health of employees. Therefore, concrete efforts are needed to raise awareness of the importance of physical activity through structured, sustainable, and task-specific physical fitness programs.